Epstein-Barr Virus microRNAs in the pathogenesis of human cancers - Caetano, Brunno Felipe Ramos; Jorge, Beatrice Adrianne Silva; Müller-Coan, Bárbara Grasiele; Oliveira, Deilson Elgui de [UNESP] (Elsevier, 2020)
The Epstein-Barr Virus (EBV) is a gamma-herpesvirus involved with a variety of human cancers, notably the endemic Burkitt lymphoma and nasopharyngeal carcinoma. In 2004, EBV was described as one the first known human oncoviruses to encode viral microRNAs (miRNAs), and these molecules were found to interact with viral and host targets. EBV miRNAs modulate biological processes that are critical for carcinogenesis, contributing to cell transformation and tumor progression of EBV-associated cancers. Herein we review and discuss EBV miRNAs as modulators of viral biology and carcinogenesis, as well as their usefulness as putative markers to monitor the onset, progression, and recurrence of cancers associated with the EBV infection.
Keywords: EBV mir-BARTs; EBV mir-BHRF1; EBERs; Nasopharyngeal carcinomas; Lymphomas; Gastric carcinomas